Quantifying Repeatability Reproducibility Sources of Error and Capacity of a Measurement: Demonstrated Using Laboratory Soil Plasticity Tests - Cheng Li; Jeramy C. Ashlock; Xuhao Wang (Advances in Civil Engineering)
The repeatability, reproducibility, and sources of error inherent in a given measurement are important considerations for potential users. To quantify errors arising from a single operator or multiple laboratories, most testing standards uses a one-way analysis of variance- (ANOVA-) based method, which utilizes a simple standard deviation across all measurements. However, this method does not allow users to quantify the sources of error and capacity (i.e., the precision to tolerance ratio). In this study, an innovative two-way ANOVA-based analysis method is selected to quantify the relative contributions of different sources of error and determine whether a measurement can be used to check conformance of a measured characteristic to engineering specifications. In this study, the standardized Atterberg limits tests, fall-cone device Atterberg limits tests, and bar linear shrinkage tests widely used for determining the soil plasticity were selected for evaluation and demonstration. Comparisons between results of the various testing methods are presented, and the error sources contributing to the overall variations between tests are discussed. Based on the findings of this study, the authors suggest use of two-way ANOVA-based R&R analysis to quantify the sources of measurement error and capacity and also recommend using the fall cone device and ASTM standardized thread rolling device for determining liquid and plastic limits of soils, respectively.